Analisis Yuridis Perlindungan Hukum Terhadap Tenaga Kerja Asing di Corporate Law Firm Indonesia - Agam Anantama Said; Rumainur Rumainur (Indo Publishing, 2026)
Globalization has driven the flow of investment and labor migration across countries, including into Indonesia. One form of this phenomenon is the presence of foreign workers (TKA) in corporate law firms. To regulate such matters, the Indonesian government issued Government Regulation Number 34 of 2021 concerning the Use of Foreign Workers. This study aims to analyze the regulation and implementation of legal protection for foreign workers in corporate law firms, as well as to identify emerging issues following the enactment of this regulation. This research employs a normative juridical approach, using secondary data obtained through literature study. The method used is a comparative approach, comparing normative provisions in the Omnibus Law and its implementing regulations. Theories applied in the analysis include the theory of justice and the theory of responsibility. This study is expected to contribute to the understanding and implementation of balanced legal protection between foreign and domestic workers in the corporate legal services sector.